Depression Stigma - Christopher Roth; Peter Schwardmann; Egon Tripodi (Center for Economic Studies and ifo Institute (CESifo), 2024)
Throughout history, people with mental illness have been discriminated against and stigmatized. Our experiment provides a new measure of perceived depression stigma and then investigates the causal effect of perceived stigma on help-seeking in a sample of 1,844 Americans suffering from depression. A large majority of our participants overestimate the extent of stigma associated with depression. In contrast to prior correlational evidence, lowering perceived social stigma through an information intervention leads to a reduction in the demand for psychotherapy. A mechanism experiment reveals that this information increases optimism about future mental health, thereby reducing the perceived need for therapy.
Keywords: 330; depression; stigma; information; psychotherapy